Outcomes of Flecainide Therapy in Rheumatic Atrial Arrhythmias: A Study on Effectiveness and Safety - Vuyyala, Balakrishna; Rasheed, Shaik Harun; bejawada, Ramya; Kavyasree, Elluri; Bhavisya, Nagineni; harini, Shikari; sadia, Seema (Journal of Neonatal Surgery, 2025)
Background: Rheumatic heart disease (RHD) results from damage to heart valves following an episode of acute rheumatic fever (ARF). This study aimed to evaluate the efficacy of flecainide in treating rheumatic atrial arrhythmias, assessing the percentage of patients who maintained sinus rhythm and identifying any adverse drug reactions (ADRs). Method: A prospective observational study was conducted over six months at Care Hospitals, Banjara Hills, Hyderabad; involving 30 patients aged 18 to 65 with various rheumatic atrial arrhythmias. Exclusions included those with structural or ischemic heart disease and individuals unwilling to participate. Results: Results indicated that rheumatic atrial arrhythmias were present in 20 patients (66.6%). The highest incidence occurred in the 50-60 age group (36.9%), with a predominance of females (63.4%). The mean age of participants was 53.8 ± 0.71 years. Among the 30 patients, 25 had atrial fibrillation; flecainide was effective in 17 patients (68%) and ineffective in 8 (32%). For the 5 patients with atrial flutter, 3 (60%) demonstrated a positive response to treatment. The most commonly prescribed dosage for maintaining sinus rhythm was 50 mg. Conclusion: In conclusion, rheumatic atrial arrhythmias are more prevalent among females and the middle-aged population. Flecainide was effective in 66.6% of cases, particularly in atrial fibrillation, with initial dosing starting at 50 mg/day, which could be increased to 150 mg/day based on clinical response.